To solve the equation \( x^2(2x - 1) + 3x(2x - 1) - 4(2x - 1) = 0 \), we can factor by recognizing that \( (2x - 1) \) is a common factor in all terms:
-
Factor out \( (2x - 1) \): \[ (2x - 1)(x^2 + 3x - 4) = 0 \]
-
Set each factor to zero:
-
For \( 2x - 1 = 0 \): \[ 2x = 1 \implies x = \frac{1}{2} \]
-
For \( x^2 + 3x - 4 = 0 \), we can factor this quadratic: \[ x^2 + 4x - x - 4 = 0 \implies (x + 4)(x - 1) = 0 \] This gives us the solutions: \[ x + 4 = 0 \implies x = -4 \] \[ x - 1 = 0 \implies x = 1 \]
-
-
Thus, the complete set of solutions to Janet's equation is: \[ x = \frac{1}{2}, -4, 1 \]
The correct response is: 1/2, -4, 1.